Legal Risks, Mitigations and Limitations Related to Electronic Contracts - Chitnis, Deepa A. (SFIMAR Research Review, 2016)
The rapid development of electronic data interchange, electronic mail and the Internet are radically affecting the way trade transactions are being conducted. A commercial transaction can be divided into three main stages: 1) The advertising and searching stage, 2) The ordering and payment stage and the 3) delivery stage. Any or all of these may be ca rried out electronically and may, therefore, be covered by the concept of 'electronic commerce'. Now in the present scenario a buyer accesses on autonomous computer controlled by a seller wherein the seller has hosted an item to be sold at a specific price, an interested buyer after satisfying himself makes an order after reading through the terms and conditions of the seller. The computer then checks the availability of the item in its stockandthen notifies the buyerthatthe orderhas been confirmed and is dispatched for its delivery after necessary payment option selected by the buyer. In such a case the actual seller of the goods is unaware about the fact that the transaction has been entered between him and the buyer. The question which arises here is thatwhethersuch contracts are valid or not. The process of moving business-fo consumer funcftons to an e-commerce modef typically involves replacing the human intermediary with software. When you allow any computer to any computer to transact directly over the Internet, the risk of infringement of rights in a business transaction becomes high. An e-contract is a contract through the offer and acceptance on the Internet, where parties concerned make use of machines and the network becomes a medium of exchanging offer and acceptance. Such electronic contracts fundamentally changed the traditional way of contracts. Th is paper asses the risks involved in such e-contracts and ways to mitigate them.